2019
DOI: 10.1097/inf.0000000000002144
|View full text |Cite
|
Sign up to set email alerts
|

Is Polymerase Chain Reaction in Neonatal Dried Blood Spots Reliable for the Diagnosis of Congenital Cytomegalovirus Infection?

Abstract: The sensitivity of CMV rt-PCR in DBS in our series was low and correlated with the bVL. Thus, a negative DBS result would not rule out cCMV infection, especially in patients with a low viremia level at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
2
2
0
1
Order By: Relevance
“…In particular, the use of saliva samples improved the inclusion rate in screening programs since many newborns had to be excluded due to unsuccessful sampling of urine [6]. Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28]. A recent study on symptomatic cCMV infections even revealed that CMV DNA levels were undetectable in 11% of whole blood samples of clinically symptomatic patients further questioning congenital CMV screening approaches based on blood samples [29].…”
Section: Discussionsupporting
confidence: 66%
“…In particular, the use of saliva samples improved the inclusion rate in screening programs since many newborns had to be excluded due to unsuccessful sampling of urine [6]. Viral load levels in EDTA blood were more than 10 4 -fold lower than in buccal swabs (Fig 3, S3 Table), consistent with the reduced sensitivity reported for assays based on dried blood spots [22,[25][26][27][28]. A recent study on symptomatic cCMV infections even revealed that CMV DNA levels were undetectable in 11% of whole blood samples of clinically symptomatic patients further questioning congenital CMV screening approaches based on blood samples [29].…”
Section: Discussionsupporting
confidence: 66%
“…High extraction rates are of no benefit if the PCR is not sensitive. Table 3 shows that the sensitivities of the PCRs for the four CMV target genes in this study are comparable to those reported by other groups, including the commercial quantitative R-gene CMV kit (also used in this study) and RealStar CMV kit [28]. This was surprising as we had designed our PCRs for genotyping of highly variable areas of the CMV genome, while the commercial kits focus purely the on detection and quantification of highly conserved CMV genes (normally UL83).…”
Section: Discussionsupporting
confidence: 85%
“…Infants are not necessarily viremic at birth. Therefore, a negative CMV PCR test for the whole blood or plasma or newborn dried blood spots (DBS) does not exclude CMV [18,19]. We concluded that intrauterine transmission had occurred for all four patients presented here.…”
Section: Discussionmentioning
confidence: 89%